Strategies to improve impact efficiency in football kicking - Peacock, J. C. A.; Ball, K. (Sports Biomechanics, 2019)
In football, kicking with high ball velocity can increase scoring opportunities and reduce the likelihood of interception. Efficient energy transfer from foot to ball during impact is important to attain a high ball velocity. It is considered impact efficiency can be increased by reducing the change in ankle plantarflexion during foot-ball impact. However, conflicting evidence exists, questioning its effectiveness as a coaching cue. The aim of the present study was to systematically analyse joint stiffness, foot velocity and impact location with a mechanical kicking machine to determine if change in ankle plantarflexion during foot-ball impact and ball velocity are influenced. Sagittal plane data of the shank, foot and ball were measured using high-speed video (4,000 Hz). Increasing joint stiffness reduced change in ankle plantarflexion and increased ball velocity from a greater effective mass. Increasing foot velocity increased change in ankle plantarflexion and increased ball velocity. Distal impact locations increased change in ankle plantarflexion and reduced ball velocity as coefficient of restitution decreased. These results identify that change in ankle plantarflexion is a dependent variable during foot-ball impact and does not directly influence ball velocity. Coaches can assess ankle motion during impact to provide feedback to athletes on their impact efficiency.